(untitled) (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. Premessa - 2. Diritto e religione in Marocco: la libertà religiosa nella Costituzione del 2011 - 3. L’apostasia nel diritto islamico: cenni - 4. Il codice penale marocchino e la fatwā del 2013 - 5. Il Consiglio Superiore degli Ulema: prerogative e valenza dei suoi interventi - 6. “La via degli Ulema” (Sabīl al-‘ulamā’) e la rinnovata interpretazione sull’apostasia - 7. Il Marocco e la “via di Marrakech”: un segnale per il futuro? Freedom of Religion and Freedom from Religion in Morocco: The Interpretative Revision on Apostasy ABSTRACT: The essay analyzes a recent step taken by the Kingdom’s Ulama that distances from the traditional meaning of apostasy and of the penalty given for this offense. According to this document, Murtadd would not be the one who leaves Islam for another religion, but the one who betrays the group he belongs to. Apostasy was therefore political, not doctrinal. In this sense, the document represents an essential progress for the qualification of religious freedom in Morocco (on the same way already indicated by the Marrakesh Declaration).